Application of drip irrigation technology for producing fruit of Salak ‘Gula Pasir” (Salacca zalacca var. Gulapasir) off season on dry land - I N Rai; I W Wiraatmaja; C G A Semarajaya; N K A Astiari (Brawijaya University, 2014)
Sugar naturally bark (Salacca zalacca var. Gulapasir) flowering every three months or four times a year, but only one or two flowering seasons are the flowers can develop into fruit. The condition causes granulated sugar fruits available in the market in a short period of time (only 2-3 months) ie at the time of harvest (on-season) from December to February, while outside the harvest season (off-season) fruit supply rare or no fruit. Occurs due to the nature of seasonal fruit Salak Sugar planted on dry land, irrigation depends only on rainfall, drought occurs when water is short so that the plant's internal water content is low and it causes a high failure rate develops into the fruit (fruit-set failure). The research aims to overcome the failure of fruit-set as drip irrigation. The study of the factors with two levels of treatment (without drip irrigation / control and with drip irrigation) during the dry season in central bark Sugar production (in Sibetan village, District Bebandem, Karangasem regency, Bali) at two harvest seasons, the season Gadu (July) and Sela II (October). Each treatment was repeated 16 times. The results showed that the plant was given a drip irrigation treatments provide fruit-set percentage was significantly higher compared with plants that are not given drip irrigation, both in summer and in winter Sela Gadu II. Percentage fruit-set on the season and Sela Gadu II in a given crop drip irrigation respectively 75.30% and 93.13%, while that does not get a drip irrigation percentage of its fruit-set each only 59.94% and 61.67%. Increased fruit-set on drip irrigation treatment is associated with increased leaf chlorophyll content, relative water content (RWC) leaves, and nutrient content of N, P, and K leaf. The increase of fruit-set led to a number of fruits and fruit weight per plant on providing drip irrigation significantly higher than the control. Based on the results of this study suggested treatment of drip irrigation can be applied to produce granulated sugar fruits out of season were planted on dry land.